Revolutionizing Expectations : Women's Organizations, Feminism, and American Politics, 1965-1980 - Blair, Melissa Estes, 1980- (Book collections on Project MUSE., 2014)
In the 1970s the women's movement created tremendous changes in the lives of women throughout the United States. Millions of women participated in a movement that fundamentally altered the country's ideas about how women could and should contribute to American society. Revolutionizing Expectations tells the story of some of those women, many of whom took part in the movement in unexpected ways. By looking at feminist activism in Durham, Denver, and Indianapolis, Melissa Estes Blair uncovers not only the workof local chapters but also the feminist activism of Leagues of Women Voters and of wome.